Diastolic Dysfunction in Neonates With Hypoxic-Ischemic Encephalopathy During Therapeutic Hypothermia: A Tissue Doppler Study - Rodriguez, Maria Jose; Martinez-Orgado, Jose; Corredera, Araceli; Serrano, Irene; Arruza, Luis (Frontiers in Pediatrics, 2022)
Diastolic dysfunction often complicates myocardial ischemia with increased mortality rates. However, less is known about diastolic function after perinatal asphyxia in neonates with hypoxic-ischemic encephalopathy (HIE) during therapeutic hypothermia (TH) and rewarming. Aim The aim of this study was to assess diastolic function with tissue Doppler imaging (TDI) in neonates with moderate–severe HIE during TH and rewarming. Method Newborns at >36 weeks' gestation with moderate–severe HIE treated with TH were evaluated with targeted neonatal echocardiography (TNE), including TDI, within 24 h of TH initiation (T1), at 48–72 h of treatment (T2), and after rewarming (T3). These retrospective data were collected and compared with a control group of healthy babies at >36 weeks' gestation that was prospectively evaluated following the same protocol. Results A total of 21 patients with HIE + TH and 15 controls were included in the study. Myocardial relaxation before the onset of biventricular filling was prolonged in the HIE + TH group during TH with significantly longer isovolumic relaxation time (IVRT') in the left ventricle (LV), the septum, and the right ventricle (RV). This was associated with slower RV early diastolic velocity (e') and prolonged filling on T1. Total isovolumic time (t-IVT; isovolumic contraction time [IVCT'] + IVRT') and myocardial performance index (MPI') were globally increased in asphyxiated neonates. All these differences persisted after correction for heart rate (HR) and normalized after rewarming. TDI parameters assessing late diastole (a' velocity or e'/a' and E/e' ratios) did not differ between groups. Conclusion TDI evaluation in our study demonstrated a pattern of early diastolic dysfunction during TH that normalized after rewarming, whereas late diastole seemed to be preserved. Our data also suggest a possible involvement of impaired twist/untwist motion and dyssynchrony. More studies are needed to investigate the impact and therapeutic implication of diastolic dysfunction in these babies, as well as to clarify the role of TH in these findings.